PENGGUNAAN GAYA MENGAJAR INKLUSI VNTUK MENGEMBANGAN DEMOKRATISASi BELAJAR DALAM PEMBELAJARAN PENDIDIKAN JASMANI DI SEKOlAH DASAR - Agus Suryobroto (LPMPP Universitas Negeri Yogyakarta, 2001)
Den10crati=afio/] ( f' learniJlg is not )Jel significulltly actualized in the teachinglearningprocess 0.1' pJlysical educatiol1 at elelnell(ary selzo()l de pite its considerableil11portance in educating learners to practice de1110Cracy. In essence democratization can betaught via classes oj' physical education at elemelltary .\·cll001 thr()ug/z to those at theulliversily level. In tIle pre..,·en( erll f' re.f()rnlation, denl()Crati=ati()11 L,' greatly needed by allJl1eJnbers 0.(society in living as a state and a nation.Tlze inclusion leae/zing style is one 0.1' tlze teaelzifzg styles in teaching physicaleducation whic/1 can give learners illus(rali()n ,' (if 11()W I() dem()crati=e. Tile anatolny oftheinclusion teaching f)f(yle consL.,,'ls (if tIle leacller making decisions be.fiJre class sessions, thelearners Inaking decisions in cla....éssions, alld tlze learners Inaking decisions after classsessions.To acfuali=e education in democruc..y ill. clas..é..'" ojjJJzy..ícal educatioll, the inclusionleae/zing style can be applied ()11 suell classes at elenlelltary school tllr()uglz to tllose at tIleuniversity level.",